Změny globální genové exprese v lidských neurálních buňkách po infekci virem klíšťové encefalitidy - Tykalová, Hana (Jihočeská univerzita, 2009)
Our study was focused on the effect of tick-borne encephalitis virus infection on global gene expression in two human neural cell lines (neuroblastoma and glioblastoma). Changes of gene expression were determined using microarray approach. We identified several genes with up-or down-regulated expression in neural cells following the infection. The changes in expression of some of them were similar in both cell lines,other exhibited different pattern.
Changes in global gene expression in human neural cells following tick-borne encephalitis virus infection
Keywords: virus klíšťové encefalititdy; exprese genů; tick-borne encephalitis virus; gene expression